Postsuburban spatial evolution of Vienna's urban fringe: evidence from point process modeling - Helbich, Marco; Leitner, Michael (Urban geography, 2010)
Metropolitan areas today are faced with pervasive changes of their urban spatial structure and are reshaped by postsuburbanization processes. In this study, one example of such postsuburban restructuring, the multinucleated monofunctional clustering of higher-order services, is investigated in the urban fringe of Vienna, Austria. The methodological framework uses microgeographic data for 2006 and applies a case-control point process modeling approach, which accounts for nonstationarity in first-order effects. The results show a relocation of highly specialized firms into the outer metropolitan ring, where these firms provide functional enrichment. This disagrees with the classical notion of a central place hierarchy. The urban fringe thus increasingly conforms to the core city. This spatial functional agglomeration shows statistically significant evidence of a bicentric urban structure, with the two new subcenters located in traditional suburban areas. Accordingly, Vienna's urban fringe is being altered by new postsuburban forms.
Elektronische Reproduktion der Druckausgabe
Gesehen am 11.04.2023